Cardiac magnetic resonance for prognostic assessment: present applications and future directions. (June 2014) - Doltra, Adelina; Schneeweis, Christopher; Fleck, Eckart; Kelle, Sebastian
Abstract : Cardiac magnetic resonance is increasingly used in clinical practice for both diagnostic and prognostic purposes. In the field of ischemic heart disease, perfusion imaging permits the assessment of ischemia, which is strongly related to future cardiac events and mortality. Late gadolinium enhancement is also associated with the prognosis and can be used as a marker of functional recovery. Cardiac magnetic resonance also permits the detection of microvascular obstruction and infarct hemorrhage, both related to an adverse outcome. In non-ischemic heart disease, the presence of late gadolinium enhancement is linked to mortality and hard events. Finally, coronary angiography, as well as new techniques, such as T1 mapping, may also have a prognostic role.